Climate Change-Induced Changes in the Chemistry of a High-Altitude Mountain Lake in the Central Alps - Steingruber, Sandra M.; Bernasconi, Stefano M.; Valenti, Giorgio (Aquatic Geochemistry, 2020)
Abstract Mountains are among the most sensitive ecosystems to climate change, and one of the most evident signs of climate-related effect is the continuous net loss of ice from the cryosphere. Several studies showed that meltwater from glaciated and perennially frozen areas can profoundly affect alpine aquatic ecosystems. Here, we present the impressive temporal increase in solutes in Lake Leit, a mountain lake in the Central Alps that is impacted by an active rock glacier. During the last 30 years, concentrations of sulfate and base cations increased by factors of 4 and 3, respectively. Atmospheric deposition, the only catchment external source, could be excluded as possible cause. The inlets have sulfate and base cations concentrations that were up to double the concentrations of the lake outlet confirming the presence of catchment internal sources. The highest concentrations were measured in the springs at the bottom of the rock glacier. Ground surface temperatures of the rock glacier indicated a high probability of permafrost occurrence, while the annual mean air temperature after the mid-1980s showed continuously positive deviations from the long-term average values (period 1961–1990) with increasing values after 2010. δ 34 S of sulfate in the inlets and the outflow indicated that sulfate in Lake Leit mainly derived from dissolution of gypsum/anhydrite even if its presence is not confirmed by the Geologic Atlas of Switzerland. Because of these results, we postulate the presence of subsurface traces of sulfate-bearing evaporites, probably associated with Triassic metasediments. These deposits are very common in the closer surroundings. We further hypothesize that the thawing of permafrost affects the flow path of water enabling its contact with fresh highly weatherable minerals increasing the overall weathering rate and shifting the relative ionic composition in the discharge toward the ions that originate from the most soluble minerals. This study shows that increased permafrost thawing in the future can influence water quality in high-alpine settings.